Virtual screening of phytochemical compounds from Physalis peruviana as perspective anti-schistosomiasis - M. Ainul Mahbubillah; Aini, Nur Sofiatul; Prastiyanto, Muhammad Evy (Generasi Biologi Indonesia, 2022)
Schistosomiasis is a neglected tropical disease (NTD) causing by a Schistosoma japonicum parasite via Oncomelania hupensis snails. Even if the the number of cases decreases significantly, there is still drawbacks of conventional medication. Physalis peruviana is promising plant that rich phytochemicals as prospective drug candidiate of schistosomiasis. This study aimed to virtually screen the inhibitory activity of anti-schistososmiasis agents derived from P. peruviana body portion. Compound data were mined from PubChem and assessed their drug properties and target prediction using SwissADME and PASSOnline. Selected phytochemical compounds were screen the pharmacokinetics and toxicity by admetsar webserver. 1,2-benzenedicarboxylic acid and docosane was final filtered compounds as promising anti-schistosomiasis target. Daily dose arrangement should be confirmed through in vitro and in vivo because of the hepatoxicity characteristics of the compounds. Protein kinases of helminth projected to be next protein target of alternative therapeutics for vital roles in organism. To be concluded, 1,2-benzenedicarboxylic acid and docosane is functioned as anti-schistosomiasis candidates with further validation in different analyses.